(untitled) (KEMANUSIAAN The Asian Journal of Humanities, 2025)
Hizbul Muslimin (HM) is a movement often labelled as a “left-wing” and supporting the communist ideology. Several questions frequently arise in relation to HM, leading to inaccurate interpretations, like supporting the communist ideology and not fighting for independence and the arrest of their leaders due to the declaration of emergency, apart from being banned by the British. However, recent British records have led to the emergence of alternative views in answering the question. This study aims to re-examine HM’s position in Malaya’s history of independence struggle. A qualitative approach, using a library research method, was adopted by examining various primary sources and secondary sources. The findings indicate that the more appropriate label for HM is a religious movement that functioned as a middle movement and adopted a strategy of cooperating with “right-wing” and “left-wing” movements. HM also rejected the communist ideology; in fact, their cooperation with the communists was just to get rid of the British. The arrest of their leaders was a double-edged sword for the British to continue their colonialism in Malaya and curb the anti-British struggle. HM was also never banned, but was instead dissolved by its own leaders. Hizbul Muslimin (HM) merupakan sebuah pertubuhan yang sering dilabel sebagai gerakan “kiri” dan menyokong ideologi komunis. Beberapa persoalan yang sering timbul berkaitan HM sehingga menimbulkan tafsiran yang kurang tepat adalah seperti menyokong ideologi komunis dan tidak memperjuangkan kemerdekaan serta penangkapan pemimpinnya yang disebabkan oleh pengisytiharan darurat, selain telah diharamkan oleh British. Namun demikian, bukti terkini daripada rekod British mengakibatkan kemunculan pandangan alternatif bagi menjawab persoalan tersebut. Objektif kajian ini adalah untuk meneliti semula kedudukan HM dalam sejarah perjuangan kemerdekaan Tanah Melayu. Kajian ini menggunakan pendekatan kualitatif, iaitu kaedah kajian kepustakaan dengan meneliti pelbagai sumber primer dan sumber sekunder. Kajian menunjukkan bahawa HM lebih sesuai dilabel sebagai gerakan agama yang berfungsi sebagai gerakan tengah dan menggunakan strategi bekerjasama dengan gerakan “kanan” dan gerakan “kiri”. HM juga menolak ideologi komunis, bahkan kerjasama dengan komunis hanyalah satu bentuk strategi politik bagi menyingkirkan British. Penangkapan pemimpin HM pula merupakan serampang dua mata British bagi meneruskan kelangsungan penjajahan mereka di Tanah Melayu serta mengekang perjuangan anti-British. HM juga tidak pernah diharamkan, sebaliknya dibubarkan oleh pemimpin mereka sendiri.